A study of local economic development in the town of Stutterheim - Dyosi, Fiona Simakuhle (Department of Political Studies, 2017)
Local economic development (LED) is progressively being implemented by developing countries and has shifted from being a development approach pursued only by industrialised nations. Academic interpretation of LED prioritises strategies based on ideas of grassroots and bottom-up development. These ideas are centred on the self-reliance of communities as well as on highlighting the benefits of creating partnerships with different actors for local development. This approach to development is encouraged in South Africa's post-apartheid local government system and is outlined in the sphere's constitutional philosophies of participatory democracy and developmental local government. As such, from the mid-1990's, LED has been embedded in legislation in South Africa, and local governments have been instructed to support LED projects and to assist in their implementation. The consensus is that the implementation of LED by South Africa's local governments has generally not been a success, and poor rural municipalities have been the most negatively impacted by these results. This dissertation looks at the evolution of LED implementation in the small rural town of Stutterheim. The first LED initiative in the town took place in the early 1990's in line with the national political transformation of South Africa from apartheid to democratic governance. This initiative has been heralded as one of the most successful cases of LED in the country. What is most noteworthy about the case is that it pre-dates the establishment of a formal post-1994 local government system and LED policy in South Africa. The LED initiative in the town has survived this formalisation but with significant revisions and reduction in its LED role in the town. This paper is primarily concerned with such revisions and the extent to which they have been a consequence of the relationship between the town's initial LED coordinator, the Stutterheim Development Foundation, and the new local government constitutionally mandated with LED. The paper further interrogates the implementation of LED in Stutterheim after 2000 and post-Stutterheim Development Foundation.